Multi-Item Flow Shop Batch Scheduling with Two Stages Dedicated Machines to Minimize Total Actual Flow Time - Ayu Anggraeni Sibarani; Dewi Tria Setyaningrum; Sugeng Waluyo (International Journal of Integrated Engineering, 2025)
A cigar manufacturing company produces two products using both shared and specialized machinery. There are 14 production stages, featuring distinct machines in Stage 2 and Stage 4. The company currently lacks a schedule, resulting in requests being fulfilled beyond the deadline. To address this issue, we developed a batch scheduling model for the flow shop, which prioritizes dedicated machines to reduce Total Actual Flow Time (TAFT). We selected the TAFT performance criteria to ensure timely completion and delivery of all orders, taking into account the maturity date. By implementing this model, the company aims to streamline operations, improve efficiency, and ultimately enhance customer satisfaction through the timely fulfillment of requests. The developed model integrates with an algorithm to address current challenges. The calculations conducted indicate that the developed model is capable of addressing batch scheduling issues for multi-stage processes with a focus on minimizing TAFT. We conducted tests on the proposed model, varying the common due dates for scenario 1 and the unit counts for scenario 2. The test results indicated that a type of product does not need to be scheduled sequentially, allowing for the ordering to be alternated with other types of products. Additionally, the batch size produced is not required to be uniform across all existing batches.